2015
DOI: 10.1063/1.4908540
|View full text |Cite
|
Sign up to set email alerts
|

Sub-band transport mechanism and switching properties for resistive switching nonvolatile memories with structure of silver/aluminum oxide/p-type silicon

Abstract: In this paper, we discuss a model of sub-band in resistive switching nonvolatile memories with a structure of silver/aluminum oxide/p-type silicon (Ag/AlxOy/p-Si), in which the sub-band is formed by overlapping of wave functions of electron-occupied oxygen vacancies in AlxOy layer deposited by atomic layer deposition technology. The switching processes exhibit the characteristics of the bipolarity, discreteness, and no need of forming process, all of which are discussed deeply based on the model of sub-band. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…However, the current of the KN film grown at 350 °C can be explained by the SCLC mechanism because, as Figure b shows, the slope of the I – V curve is close to 1.0 for a low electric field and changes to approximately 2.0 for a high electric field. For the SCLC conduction mechanism, the interface between the TiN electrode and the KN film needs to be conductive . Therefore, it is considered that many defects, such as oxygen vacancies, are formed in the KN film near the KN/TiN interface after the set process, and decreased the barrier height of the KN/TiN interface, resulting in the formation of quasi-conductive KN/TiN interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current of the KN film grown at 350 °C can be explained by the SCLC mechanism because, as Figure b shows, the slope of the I – V curve is close to 1.0 for a low electric field and changes to approximately 2.0 for a high electric field. For the SCLC conduction mechanism, the interface between the TiN electrode and the KN film needs to be conductive . Therefore, it is considered that many defects, such as oxygen vacancies, are formed in the KN film near the KN/TiN interface after the set process, and decreased the barrier height of the KN/TiN interface, resulting in the formation of quasi-conductive KN/TiN interface.…”
Section: Resultsmentioning
confidence: 99%
“…For the SCLC conduction mechanism, the interface between the TiN electrode and the KN film needs to be conductive. 49 Therefore, it is considered that many defects, such as oxygen vacancies, are formed in the KN film near the KN/TiN interface after the set process, and decreased the barrier height of the KN/TiN interface, resulting in the formation of quasi-conductive KN/TiN interface. Figure S9d of Section 9 in the Supporting Information shows that the SCLC mechanism can also explain the I−V curve in HRS before the set process, which was obtained when the negative voltage was applied to the Pt top electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, in the HRS, a relatively high current of 80 pA was obtained at the same position of the NKN film, as shown in Figure d, and this high current may be due to the presence of the remnant filament. This result indicated that the high current of the 200 °C‐grown NKN film in HRS may be explained by the presence of the remnant filament …”
Section: Nkn Reram Devicesmentioning
confidence: 92%
“…The negative voltage was applied to the Pt top electrode. The current‐conduction mechanisms of the dielectric films are generally considered to be Schottky emission (SE), Poole–Frenkel emission (PFE), and space‐charge‐limited conduction (SCLC) . According to the Supporting Information (see Figure S5a–c), the conduction behavior of this NKN film in the HRS can be explained by the SE in a low electric field (<0.1 MV cm −1 ), and by the PFE in a high electric field (>0.1 MV cm −1 ), as shown in Figure a.…”
Section: Nkn Reram Devicesmentioning
confidence: 99%
“…Furthermore, because the Al 2 O 3 layers can be simply deposited using physical vapor deposition processes at room temperature, it can offer promising possibilities to be utilized in flexible memory systems . Although a number of studies have been conducted to secure reliable electrical performances of Al 2 O 3 memory devices for a practical storage medium, further investigations are required to satisfy their repetitive stability . To address these issues, multilayer active structures have been proposed beyond the strategies employing interface treatments or a bi‐layer active structure .…”
Section: Introductionmentioning
confidence: 99%